Disclosure of Personalized Rheumatoid Arthritis Risk Using Genetics, Biomarkers, and Lifestyle Factors to Motivate Health Behavior Improvements: A Randomized Controlled Trial. Issue 6 (16th April 2018) - Sparks, Jeffrey A.; Iversen, Maura D.; Yu, Zhi; Triedman, Nellie A.; Prado, Maria G.; Miller Kroouze, Rachel; Kalia, Sarah S.; Atkinson, Michael L.; Mody, Elinor A.; Helfgott, Simon M.; Todd, Derrick J.; Dellaripa, Paul F.; et al.
Abstract : Objective: To determine the effect of disclosure of rheumatoid arthritis (RA) risk personalized with genetics, biomarkers, and lifestyle factors on health behavior intentions. Methods: We performed a randomized controlled trial among first‐degree relatives without RA. Subjects assigned to the Personalized Risk Estimator for Rheumatoid Arthritis (PRE‐RA) group received the web‐based PRE‐RA tool for RA risk factor education and disclosure of personalized RA risk estimates, including genotype/autoantibody results and behaviors (n = 158). Subjects assigned to the comparison arm received standard RA education (n = 80). The primary outcome was readiness for change based on the trans‐theoretical model, using validated contemplation ladder scales. Increased motivation to improve RA risk–related behaviors (smoking, diet, exercise, or dental hygiene) was defined as an increase in any ladder score compared to baseline, assessed immediately, 6 weeks, and 6 months post‐intervention. Subjects reported behavior change at each visit. We performed intent‐to‐treat analyses using generalized estimating equations for the binary outcome. Results: Subjects randomized to PRE‐RA were more likely to increase ladder scores over post‐intervention assessments (relative risk 1.23, 95% confidence interval [95% CI] 1.01, 1.51) than those randomized to nonpersonalized education. At 6 months, 63.9% of PRE‐RA subjects and 50.0% of comparison subjects increased motivation to improve behaviors (age‐adjusted difference 15.8%; 95% CI 2.8%, 28.8%). Compared to nonpersonalized education, more PRE‐RA subjects increased fish intake (45.0% versus 22.1%; P = 0.005), brushed more frequently (40.7% versus 22.9%; P = 0.01), flossed more frequently (55.7% versus 34.8%; P = 0.004), and quit smoking (62.5% versus 0.0% among 11 smokers; P = 0.18). Conclusion: Disclosure of RA risk personalized with genotype/biomarker results and behaviors increased motivation to improve RA risk–related behaviors. Personalized medicine approaches may motivate health behavior improvements for those at risk for RA and provide rationale for larger studies evaluating effects of behavior changes on clinical outcomes, such as RA‐related autoantibody production or RA development.